Potential mobility of inorganic nutrients and its controls at the sediment-water interface in the main path of Kuroshio Current off eastern Taiwan. Issue 1 (15th June 2017) - Zhou, Fengxia; Gao, Xuelu; Zhang, Yong; Yuan, Huamao; Song, Jinming; Liu, Kai; Yang, Bo; Zhuang, Wen
Abstract: Surface sediments were collected from the main path of Kuroshio Current (KC) off eastern Taiwan (ETW), and laboratory incubation was conducted for the study of the nutrient exchange at the sediment-water interface. Exchange fluxes of NO3 − -N, NO2 − -N, NH4 + -N, PO4 3 − -P and SiO3 2 − -Si under simulated site condition were − 0.0866, 0.00146, 0.0634, − 0.00812 and − 0.181 mmol m − 2 d − 1, respectively. This indicated that sediments in the studied area might act as a source of NO2 − -N and NH4 + -N and a sink of NO3 − -N, PO4 3 − -P and SiO3 2 − -Si. Factors affecting nutrient exchange fluxes were studied by changing incubation conditions. Compared with some coastal areas in China, the main path of KC off ETW showed relatively low nutrient exchange fluxes at the sediment-water interface. It could be inferred that the sediment-water exchange of nutrients in the main path of KC off ETW had little influence on the downstream nutrient transportation by KC year-round based on the results of this research. Highlights: Sediments off eastern Taiwan were sampled and tested as sink or source of nutrients. Factors affecting nutrient fluxes were examined by changing incubation conditions. Sediments there might have little impact on nutrient transport by Kuroshio Current.